A surface-modified basalt fiber reinforced polymer-based adhesive, composite material, and preparation method and application thereof
By performing surface modification treatment on basalt fibers, the problem of poor interfacial compatibility between fibers and polymer matrix is solved, the strength and processability of composite materials are significantly improved, and its application in pipeline reinforcement and other fields is expanded.
Patent Information
- Application Number
- CN202411851234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-01
AI Technical Summary
The surface of the basalt fibers is smooth and have low chemical activity, resulting in poor interface compatibility with the polymer matrix, affecting the overall performance of the composite material.
By performing surface modification treatment on basalt fiber particles, including deionized water cleaning, heat treatment, deslurry activation and polyaniline modification, the interface bond strength between the fiber and the matrix is improved.
It enhances the interface bonding between basalt fibers and resin matrix, improves the overall strength, toughness and processability of the composite material, and is suitable for applications such as pipeline reinforcement.
Smart Images

Figure CN119736796A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of basalt fiber reinforced composite materials, and relates to a surface modified basalt fiber reinforced polymer-based adhesive, a composite material, and a preparation method and application thereof. Background Art
[0002] High modulus polymer-based composites are widely used in the aerospace field due to their high strength and stiffness, low weight and excellent fatigue properties. At present, carbon fiber reinforced polymer-based composites (CFRP) are widely used in the fuselage structure of long-range aircraft such as Airbus A350 and Boeing 787, accounting for more than 50% of the weight. In automotive structures, such as body panels, roof and floor components, high modulus polymers are used because of their advantages in reducing vehicle weight and improving performance. In wind turbine applications, carbon fiber has excellent aerodynamic performance due to its high specific modulus, which allows longer blades and slimmer designs. As the advantages of polymer-based composites in processing and aesthetics become more and more prominent, their application in the construction field is also increasing, such as 3D-printed 100% polymer composite panels, which have unique advantages of multi-functions such as structure, insulation, MEP integration, air / moisture / fire barriers and interior / exterior finishes. In addition, high-strength fibers are also used to repair and reinforce buildings, increase the load-bearing capacity of floors and columns, and resist earthquake damage. In the fields of aerospace hydrogen tanks, hydrogen fuel cell systems, natural composite material batteries, etc., high modulus polymer-based composite materials are also expanding their applications to improve their mechanical properties. With the demand for environmental protection and green development, high modulus polymer-based composite materials are also widely used in the field of infrastructure. Such as the reinforcement of bridges, roads and tunnels to improve the bearing capacity and durability of the structure. In addition, high-strength polymer mortar can be used for basement leakage resistance, building roof and internal and external wall leakage resistance, various pools and swimming pools seepage resistance projects, tunnels, granaries, factories, enclosed balconies, etc. In summary, by preparing a variety of high modulus polymer-based composite materials, it can provide high-performance solutions while promoting technological progress in related industries.
[0003] When basalt fiber is used as a reinforcement to reinforce composite materials, it exhibits excellent mechanical properties, such as light weight, high breaking strength, good tensile strength, and high ultimate tensile strain. At the same time, it has excellent chemical corrosion resistance, especially in acidic and alkaline media. Its low moisture absorption rate (0.2%-0.3%) and good water resistance can ensure the chemical stability, long life and environmental coordination of the material. In addition, the raw materials for the production of basalt fiber are taken from natural volcanic rocks, without additives, and no "three wastes" are discharged during the production process. It has little pollution to the environment and is an environmentally friendly and energy-saving product. Basalt fiber has good high temperature resistance, excellent insulation and low thermal conductivity, and is suitable for applications that require thermal insulation and electrical insulation. Basalt fiber has good physical and chemical compatibility when compounded with various materials (such as metals, resins, etc.), and has stronger bonding strength than glass fiber, carbon fiber, etc. In addition, basalt fiber composite materials are degradable, non-toxic, and non-polluting to the environment compared to glass fiber and carbon fiber reinforced composite materials. These advantages make basalt fiber reinforced composites have broad application prospects in many fields, such as civil engineering, aerospace, and military industry.
[0004] However, basalt fiber has a smooth surface and low chemical activity, showing strong chemical inertness, poor wettability with the matrix resin, and it is difficult to produce a good interface bonding with the polymer matrix, resulting in poor interface compatibility of the composite material. This poor interface compatibility will cause the overall performance of the composite material to be unable to fully exert the mechanical properties of basalt fiber, affecting the various properties of the composite material. At present, there are mainly the following methods for surface modification of basalt fiber: 1) Plasma modification, through plasma sputtering and etching on the fiber surface, increasing the surface roughness, improving the interface bonding energy between the modifier and the fiber, while not damaging the main performance and structure of the fiber; 2) Acid-base etching modification, soaking the fiber in an acidic or alkaline solution, through the acid and alkaline solution and the oxide in the fiber component to react, forming grooves on the surface, increasing the number of surface silanol groups and roughness, and improving the interface bonding force between the fiber and the matrix; 3) Coupling agent modification treatment, using a coupling agent such as KH-550 to modify the surface of basalt fiber, can improve High fiber surface roughness and wettability, enhance the friction between the fiber and the composite matrix, and improve the physical, mechanical and thermal properties of the composite material; 4) Surface coating modification, coating other substances on the fiber surface, introducing new functional groups, and at the same time playing the role of a protective layer on the fiber surface, improving the chemical inertness of the fiber surface, increasing the surface roughness, eliminating interfacial stress, and increasing the bonding force between the fiber and the matrix; 5) Nano-SiO2 surface modification, using nano-SiO2 to modify the surface of basalt fiber can improve the micro-nano structure of the fiber, reduce defects such as cracks and bubbles inside the fiber, and improve the interlaminar shear strength between the matrix and the fiber and the performance of the composite material. These methods help to prepare composite materials with excellent performance by improving the surface activity, strength and interfacial bonding of basalt fibers. However, the research on the surface modification of basalt fibers is still immature, and the overall performance of basalt fiber-reinforced polymer-based composites does not meet the application requirements, which greatly limits its demand for further application in more fields. Summary of the invention
[0005] In view of this, the purpose of the present invention is to address the problems existing in the background technology and propose a surface modified basalt fiber reinforced polymer-based adhesive, a composite material, and a preparation method and application thereof.
[0006] It should be noted that the present invention improves the interface bonding strength between the fiber and the matrix by modifying the surface of the basalt fiber, which is currently an effective means to improve the performance of basalt fiber reinforced polymer-based composite materials. Based on this, a new basalt fiber surface modification method is provided to obtain a new basalt fiber reinforced polymer-based composite material, which is of great value in expanding the application field of basalt fiber and providing new high-performance composite materials in the field of high-tech.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The first technical purpose of the present invention is to provide a surface modification method of basalt fiber, which specifically comprises the following steps:
[0009] 1) Clean the surface of basalt fiber particles with deionized water and dry them for later use;
[0010] 2) placing the basalt fiber particles in a drying oven at a temperature of 200-250° C. for 1-3 hours to remove the sizing agent on the fiber surface; cooling naturally after the heat treatment, dispersing them in an acetone solution, and stirring for 20-60 minutes; filtration and separation, washing with deionized water, and drying at 80° C.-100° C. for 3-5 hours to obtain desizing and activated basalt fiber particles;
[0011] It should be noted that if the drying oven temperature is lower than this temperature or the heat treatment time is shorter than this time, the surface wetting agent will not be completely removed, which will lead to incomplete subsequent desizing and affect the processability and structural properties of the final composite material; if the temperature is higher than this temperature or the time is longer than this time, the energy consumption is high and the efficiency is low.
[0012] In addition, the heat-treated basalt fiber particles are dispersed in an acetone solvent, and the ratio of the fiber particles to the acetone solvent is treated at a weight ratio of 1:4-8, and the stirring time is 20-60 minutes. If the ratio is lower than this, a large amount of solvent is used, resulting in a waste of resources and increasing the difficulty of subsequent solvent recovery; if the ratio is higher than this, the fiber particles cannot be fully immersed in the solvent to achieve complete desizing, which affects the subsequent preparation and performance of the composite material; and if the stirring time is lower than this range, the infiltration and desizing treatment is insufficient, and if it is longer than this time, the energy consumption is increased and the efficiency is low.
[0013] 3) dissolving the polyaniline powder in xylene, stirring evenly to obtain a polyaniline solution with a mass fraction of 0.25-3%, adding the activated basalt fiber particles obtained in step 2) to the polyaniline solution at a mass ratio of 3:8-12, stirring and blending for 40-90 minutes, centrifuging, placing in a fume hood to air dry, and then placing in a drying oven at a temperature of 100-120° C. for 1-3 hours to obtain polyaniline-modified basalt fiber particles.
[0014] It should be noted that the solution has a mass fraction of 0.25-3%. If the solubility is lower than this, the amount of solvent used is too large, and the subsequent treatment of the fiber particles requires a long time to ensure that the fiber surface has a loading amount of the modifier that meets the requirements; if the concentration is higher than this, polyaniline cannot be effectively dissolved and dispersed, the solution viscosity is high, and it is difficult to control the uniform and sufficient loading of polyaniline on the fiber surface.
[0015] In addition, the mass ratio of basalt fiber particles to polyaniline solution is 3:8-12. If it is lower than this ratio, the amount of polyaniline solution used is large, resulting in waste of resources and increasing the cost of waste treatment in the later stage. If it is higher than this ratio, the fiber particles cannot be fully dispersed, and the loading amount of the treatment agent on the surface of the fiber particles cannot be controlled. The stirring and blending time of the two is 40-90 minutes. If it is shorter than this time, the loading of polyaniline on the fiber surface is uneven and insufficient, affecting the performance of the subsequent composite material. If it is longer than this time, the efficiency is low.
[0016] The second technical purpose of the present invention is to provide a basalt fiber reinforced polymer-based composite glue, wherein the polymer-based glue is prepared by adding the above-mentioned surface-modified basalt fiber particles to an epoxy resin, wherein the mass ratio of the surface-modified basalt fiber particles in the epoxy resin matrix is 5-15%, and after being stirred evenly, the blended system is placed in an ultrasonic cleaning machine for treatment for 40-60 minutes, and then a curing agent is added and slowly stirred evenly, and the mixture is further treated in the ultrasonic cleaning machine for 5-10 minutes to obtain a basalt fiber reinforced polymer-based composite glue.
[0017] It should be noted that the epoxy resin is various types of commercial epoxy resin, the curing agent is triethylenetetramine, and the amount of curing agent is calculated based on the epoxy value; the mass ratio of the basalt fiber particles after surface modification in the epoxy resin matrix is 5%-15%, below this ratio, the basalt fiber particles have no obvious effect on improving the structural strength of epoxy resin-based composite materials; above this ratio, the volume proportion of basalt fiber in the epoxy resin polymer is too large, resulting in a sharp increase in the viscosity of the glue and poor fluidity, making it impossible to perform processing operations such as casting and coating, and cannot be used for process operations of pipeline reinforcement.
[0018] In addition, the processing time of the blending system in the ultrasonic cleaning machine is 40-60 minutes. If it is shorter than this time, the bubble defects introduced by the addition of basalt fiber particles cannot be removed, resulting in low structural strength of the subsequent composite material; if it is longer than this time, the energy consumption is high and the efficiency is low. The processing time after adding the curing agent is 5-10 minutes. If it is shorter than this time, the bubble defects cannot be effectively removed. If it is longer than this time, the system undergoes polymerization reaction, resulting in increased viscosity of the glue, making it difficult to perform pipeline reinforcement operations or transfer to the mold for molding.
[0019] The third technical purpose of the present invention is to provide the use of the basalt fiber reinforced polymer-based composite glue prepared by the method as described above in pipeline reinforcement.
[0020] The fourth technical purpose of the present invention is to provide a basalt fiber reinforced polymer-based composite material. The basalt fiber reinforced polymer-based composite glue prepared above is slowly and evenly poured into a mold, left to stand at room temperature for 2-5 minutes, transferred to a drying oven, and cured at 80-100°C for 40-60 minutes to complete curing and molding, thereby obtaining the basalt fiber reinforced polymer-based composite material.
[0021] It should be noted that the 2-5 minutes of standing at room temperature is to allow the glue to spread evenly in the mold so as to obtain a regular composite material; if it is longer than this time, the efficiency is low, and the basalt fiber particles may settle, affecting the structural strength of the subsequent composite material.
[0022] In addition, the molding temperature is 80-100℃, and the curing time is 40-60min. If the temperature is lower than this or the time is shorter than this, the curing rate is slow, the curing is incomplete, and the performance of the composite material is poor; if the temperature is higher than this or the time is longer than this, the curing reaction rate is too fast, the internal curing is uneven, the curing efficiency is low, and the performance of the composite material is poor.
[0023] The fifth technical purpose of the present invention is to provide the use of the basalt fiber reinforced polymer-based composite material as described above in a pipeline impact-resistant structural bearing member.
[0024] The present invention discloses a method for surface modification of basalt fiber and a method for preparing a basalt fiber reinforced polymer-based composite material, wherein polyaniline is in-situ loaded on the surface of basalt fiber to construct a rough surface containing active functional groups, and the rough surface is used to enhance the interface bonding between basalt fiber and polymer matrix, thereby obtaining a polymer-based composite material that is easy to process, has excellent modulus, and has outstanding impact resistance. The composite material is easy to shape and its application in the field of pipeline reinforcement is expanded to solve the problems of low practicality of existing basalt fiber surface modification methods, poor performance of composite materials, and limited application.
[0025] It can be seen from the above technical solutions that, compared with the prior art, the surface-modified basalt fiber-reinforced polymer-based adhesive, composite material, and preparation method and application thereof provided by the present invention have the following excellent effects:
[0026] The present invention uses a simple surface treatment technology and method to perform surface modification treatment on basalt fiber particle powder, and then disperses it evenly in an epoxy resin matrix by ultrasonic assisted dispersion to obtain a polymer glue suitable for pipeline reinforcement, and then obtains a polymer-based composite material with outstanding structural performance through curing and molding.
[0027] Compared with the existing fiber surface treatment and composite material molding and application, the present invention solves the following three problems:
[0028] 1) Enhanced interfacial bonding between basalt fiber and resin matrix: By surface modification of basalt fiber particles, its surface activity is improved, thereby enhancing its compatibility with epoxy resin matrix. This modification can effectively reduce interface defects and improve the overall strength and toughness of the composite material.
[0029] 2) Improved dispersibility of micro powder: Ultrasonic assisted dispersion technology is used to evenly disperse the modified basalt fiber particles in the epoxy resin, avoiding the aggregation and precipitation phenomena common in traditional methods. This improvement makes the composite material perform better in terms of mechanical properties and durability.
[0030] 3) Simplified production process: The surface treatment and dispersion methods used in the present invention are relatively simple and easy to operate, and can reduce production costs and cycles.
[0031] Compared with the prior art, the present invention has obvious advantages in production efficiency and economy, and is suitable for large-scale industrial applications.
[0032] In summary, the polymer-based composite material of the present invention shows significant advantages in performance and production process and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0034] Figure 1 Surface treatment of basalt fiber particle powder: (a) basalt fiber powder, (b) activated basalt fiber powder, (c) basalt fiber powder treated with siloxane coupling agent, (d) basalt fiber powder treated with waterborne polyurethane, (e) basalt fiber powder treated with polyaniline (0.5%), (f) basalt fiber powder treated with polyaniline (1%), (g) basalt fiber powder treated with polyaniline (2%), (h) basalt fiber powder treated with polyaniline (3%).
[0035] Figure 2 Infrared test of basalt fiber particle powder; BF powder: basalt fiber particle powder, BF powder surface activation: basalt fiber powder after surface activation treatment, KH550: basalt fiber powder treated with siloxane coupling agent, PU: basalt fiber powder treated with water-based polyurethane, PANI: basalt fiber powder treated with polyaniline.
[0036] Figure 3 The cross-sectional morphologies of basalt fiber particles reinforced polymer-based composites after surface treatment by different treatment methods; (a) basalt fiber particles treated with siloxane coupling agent, (b) basalt fiber particles treated with waterborne polyurethane, (c) basalt fiber particles treated with polyaniline, (a-1) basalt fiber particles treated with siloxane coupling agent (enlarged), (b-1) basalt fiber particles treated with waterborne polyurethane (enlarged), (c-1) basalt fiber particles treated with polyaniline (enlarged).
[0037] Figure 4 The bending strength and tensile modulus of basalt fiber particle reinforced polymer-based composites after surface treatment in different treatment methods; KH-550: basalt fiber powder treated with siloxane coupling agent, PU: basalt fiber powder treated with water-based polyurethane, PANI: basalt fiber powder treated with polyaniline.
[0038] Figure 5 The tensile strength and tensile modulus of basalt fiber particles reinforced polymer-based composites after surface treatment in different treatment methods; KH-550: basalt fiber powder treated with siloxane coupling agent, PU: basalt fiber powder treated with water-based polyurethane, PANI: basalt fiber powder treated with polyaniline.
[0039] Figure 6 Impact strength of basalt fiber particles reinforced polymer-based composites after surface treatment in different ways: KH550; basalt fiber powder treated with siloxane coupling agent, PU: basalt fiber powder treated with water-based polyurethane, PANI: basalt fiber powder treated with polyaniline. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The embodiment of the invention discloses a method for preparing a basalt fiber reinforced polymer-based composite material.
[0042] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0043] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0044] Examples 1-6
[0045] A preparation method of a basalt fiber reinforced polymer matrix composite material comprises the following steps:
[0046] 1. Use deionized water to clean the surface of basalt fiber particles and dry them for later use;
[0047] 2. Place the basalt fiber in a drying oven and heat treat it at a temperature of 200-250°C for 1-3 hours to remove the wetting agent on the fiber surface; after the heat treatment is completed, cool it naturally, and then disperse it in an acetone solution at a weight ratio of 1:(4-8), and stir it for 20-60 minutes; after filtration and separation, rinse it with deionized water and dry it at 80°C for 3-5 hours to obtain desizing and activated basalt fiber particles.
[0048] 3. The polyaniline powder is dissolved in xylene to prepare a polyaniline solution with a mass fraction of 0.25-3%. After uniform dissolution, the desizing and activated basalt fiber particles are added to the polyaniline solution at a mass ratio of 1:(3-4), stirred and blended for 40-90 minutes, centrifuged, placed in a ventilated kitchen to air dry, and then placed in a drying oven at 120° C. for 1 hour to obtain polyaniline-modified basalt fiber particles.
[0049] 4. Weigh epoxy resin and add polyaniline-modified basalt fiber particles, wherein the mass ratio of the surface-modified basalt fiber particles in the epoxy resin matrix is 5-15%. After stirring evenly, place the blended system in an ultrasonic cleaner for 40-60 minutes; then add curing agent triethylenetetramine, slowly stir evenly, and continue to treat in the ultrasonic cleaner for 5-10 minutes to obtain basalt fiber-reinforced polymer-based composite glue, which can be used for pipeline reinforcement.
[0050] 5. Slowly and evenly pour the basalt fiber reinforced polymer-based composite glue into the mold, let it stand at room temperature for 2-5 minutes, transfer it to a drying oven, and cure it at 80-100°C for 40-60 minutes to complete the curing and molding, thereby obtaining a basalt fiber reinforced polymer-based composite material.
[0051] Comparative Examples 1-4
[0052] The comparative study was conducted from three aspects: the type of surface modifier, the amount of surface modifier used, and the content of modified basalt fiber particles in the epoxy resin matrix.
[0053] The material proportions in Examples 1-6 and Comparative Examples 1-4 are as follows:
[0054] Table 1 Material ratio in Examples 1-6
[0055]
[0056] Note: The mass of basalt fiber after activation treatment is obtained by weighing the basalt fiber particle sample after desizing and activation treatment;
[0057] Table 2 Material ratios in comparative examples 1-4
[0058] Serial number Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Basalt fiber mass (g) 5 5 5 5 Drying oven temperature (℃) 200 200 200 200 Heat treatment time (h) 1 1 1 1 Acetone dosage (g) 20 40 30 25 Stirring time (min) 30 30 30 30 Drying time at 80℃(min) 3 4 5 3 Mass of activated basalt fiber particles (g) 4.75 4.79 4.72 4.8 Mass fraction of polyaniline solution 4% 0.5% Mass fraction of siloxane coupling agent solution 0.5% - - - Mass fraction of waterborne polyurethane solution - 0.5% - - Surface modifier dosage (g) 16 16 - 16 Stirring and blending time in modifier solution (min) 50 40 - 40 Mass fraction of modified basalt fiber particles in epoxy resin 10% 10% - 18% Ultrasonic treatment time (min) 50 40 - 40 Ultrasonic treatment time after adding curing agent (min) 8 8 - 8 Curing temperature (℃) 100 100 - 80 Curing time (min) 40 40 - 50
[0059] Note: When the mass of the designed polyaniline solution is 4%, polyaniline becomes a viscous gel in xylene and subsequent surface modification operations cannot be performed.
[0060] In order to investigate the application effect of the polymer-based composite glue and composite materials prepared by the method of the present invention in pipeline reinforcement, the composite materials obtained in Examples 1-6 and Comparative Examples 1-4 were subjected to viscosity tests, fluidity tests, bending strength and modulus tests, tensile strength and modulus tests, impact strength tests, and surface micromorphology characterization.
[0061] The apparent viscosity of the composite material was tested by a rotational viscometer and in accordance with the standard GB / T 2794-2013, and the process feasibility of the composite material in pipeline reinforcement application was evaluated by measuring the flow distance of the resin glue under standard conditions within a specified time. At room temperature, 2g of epoxy resin glue was dropped on the center of a smooth horizontal glass plate with a diameter of 10cm. After it flowed freely for 1min, the distance from the center position was measured as an evaluation index of its fluidity. The results are shown in Table 3.
[0062] Table 3 Apparent viscosity and fluidity of the composite materials prepared in Examples 1-6 and Comparative Examples 1-4
[0063]
[0064]
[0065] The apparent viscosity of the resin can directly reflect the viscosity of the epoxy resin system. Among them, the glue with a viscosity in the range of 3000-8000Pa.s has a certain fluidity and can be molded by casting, coating, hand lay-up and other processes. The intuitive flow distance parameter can evaluate the feasibility of the glue in the coating molding operation. The flow distance in the range of 2-8cm indicates that the glue has excellent fluidity and is suitable for coating and reinforcement treatment of the pipeline surface. Among them, as the content of modified basalt fiber particles in epoxy resin increases, the surface viscosity of the resin glue increases and the flow distance decreases. Comparative analysis of Example 4 and Example 5 shows that after adding the curing agent, the extension of the ultrasonic time will increase the viscosity of the resin system and reduce the flow distance.
[0066] (1) The microscopic morphology of the surface-modified basalt fiber particles was characterized using a scanning electron microscope. Figure 1 shown.
[0067] The characterization of the surface morphology of basalt fiber can intuitively compare the effects of different surface treatment methods on its microstructure. Comparative analysis of the activated modified basalt fiber particles and the original samples shows that the activation treatment removes impurities on the particle surface, which can also explain the phenomenon of reduced sample mass after activation treatment. Figure (b) and Figure (c) are the micromorphologies of basalt fiber particles modified with siloxane coupling agent and waterborne polyurethane, respectively. Corresponding to Comparative Example 1 and Comparative Example 2, it can be found that there is no obvious modifier loading on the surface of the modified basalt particles. By comparing the surface of the basalt fiber particles treated with polyaniline modifier (Figure eh), it can be found that polyaniline is loaded on the surface of the basalt fiber particles, and as the concentration of the polyaniline modified solution increases, the surface loading gradually increases. After the surface of the basalt fiber particles is loaded with the modifier, the surface is obviously roughened, and the rough surface can significantly improve the interfacial bonding between the fiber and the resin matrix, thereby improving its structural properties.
[0068] (2) The surface functional group structure of the surface-modified basalt fiber particles was characterized using an infrared spectroscopy test instrument. The results are as follows: Figure 2 shown.
[0069] The characterization of the surface functional group structure of the modified basalt fiber can reflect whether the surface modification treatment is achieved and the type of surface functional groups. By comparing the samples modified by different modifiers, it can be found that the basalt fiber particles treated with polyaniline modifier have obvious absorption peaks of aniline structure on the surface, while the unmodified system and the samples modified with coupling agent and polyurethane do not have the absorption peaks of 1500 and 1433 cm -1 The functional group absorption peak at , once again proves that there are more reactive groups on the surface of basalt fiber particles after polyaniline modification, which can form a strong interface bonding effect with the epoxy resin matrix.
[0070] (3) The cross-sectional morphology of the surface-modified basalt fiber particle reinforced epoxy resin-based composite material was tested and characterized using a scanning electron microscope. The results are as follows: Figure 3 shown.
[0071] By characterizing the cross-sectional morphology of the composite material, the dispersion state of the basalt fiber particles in the epoxy resin matrix and the interface bonding between the fiber particles and the resin matrix can be explained.
[0072] Depend on Figure 3It can be seen that the basalt fiber particles treated with polyaniline are evenly dispersed in the resin matrix, and there are no obvious voids and gaps between the fiber and the resin matrix, indicating that the interface bonding between the fiber and the resin matrix has not been destroyed under the fracture load. Comparing the cross-sectional morphology of the composite material modified with siloxane coupling agent and polyurethane modifier with the polyaniline modified system, it can be found that the fiber dispersion uniformity and interface bonding are more prominent in the polyaniline modified system.
[0073] (4) The bending properties of the composite materials were tested using an electronic universal testing machine and in accordance with the standard GB / T 1040-2006. The rate was 10 mm / min and each group of samples was tested 5 times to obtain the average value. Figure 4 shown.
[0074] (5) The tensile properties of the composite materials were tested using an electronic universal testing machine in accordance with the standard GB / T 1447-2005 at a rate of 2 mm / min. Each group of samples was tested 5 times to obtain the average value. Figure 5 shown.
[0075] (6) The impact properties of the composite materials were tested using a digital pendulum impact tester in accordance with the standard GB / T 1843-1996. Each group of samples was tested 5 times to obtain the average value. Figure 6 shown.
[0076] Table 4 Structural performance parameters of the composite materials obtained in Examples 1-6 and Comparative Examples 1-4
[0077]
[0078] Note: In Comparative Example 3, the viscosity of the polyaniline modifier was too high to perform surface modification on the basalt fiber and thus a composite material could not be prepared; in Comparative Example 4, the viscosity of the modified basalt fiber reinforced epoxy resin-based glue was too high to be transferred to the mold, and a composite material that could be used to test mechanical properties could not be obtained.
[0079] By testing and characterizing the flexural strength / flexural modulus, tensile strength / tensile modulus, and impact strength of composite materials, the structural strength of the composite materials can be effectively evaluated, and then their suitability for application in the field of pipeline reinforcement can be evaluated.
[0080] Comparative analysis of the flexural strength and modulus of the composite materials in the examples shows that as the content of modified basalt fiber particles in the composite material increases, the flexural strength and modulus of the composite material gradually increase. However, Example 5 shows a decrease in flexural strength and modulus, mainly because the content of basalt fiber particles is large, and the ultrasonic assisted dispersion time after adding the curing agent is relatively short, so that the bubble defects in the system cannot be completely discharged, and a small amount of void defects appear inside the composite material, resulting in a slight decrease in the bending performance.
[0081] Comparing Comparative Example 5 and Example 6, it can be found that the flexural strength and modulus of the composite material prepared in Example 6 are slightly improved, which is mainly because the content of the polyaniline modifier in Example 6 is relatively high, which further improves the interface bonding between the basalt fiber particles and the epoxy resin matrix, so that the flexural properties of the composite material are improved. Among them, the flexural modulus of the composite material prepared in Example 6 is the largest, which is mainly attributed to the appropriate amount of fiber particles added, the appropriate time of ultrasonic assisted dispersion, and the appropriate content of polyaniline modifier to modify the fiber surface.
[0082] By comparing and analyzing the tensile strength, modulus and impact strength of the composite materials in the examples, it can be found that the tensile properties and impact properties show similar rules to the bending properties. This is because the main factors affecting the tensile properties and impact properties of the composite materials are similar to the bending properties, mainly including the interfacial bonding effect between the fiber particles and the resin matrix, the uniformity of the fiber dispersion in the resin matrix, and the number of defects inside the composite material.
[0083] From the mechanical properties of the composite materials in the comparative examples, it can be seen that the composite material reinforced by basalt fiber particles modified by siloxane coupling agent (Comparative Example 1) shows the lowest bending strength / modulus and tensile strength / modulus, while its impact strength performance is relatively good, mainly because siloxane coupling agent, as a kind of traditional glass fiber surface modifier, has poor compatibility with basalt fiber and fails to improve the interface bonding between basalt fiber particles and epoxy resin matrix. The impact strength performance is outstanding, mainly because siloxane coupling agent, as a kind of rigid structure polymer, plays the role of rigid segment in epoxy resin polymer, improves the rigidity of the system, and thus shows the improvement of impact strength. The composite material reinforced by basalt fiber particles modified by waterborne polyurethane (Comparative Example 2) shows moderate bending performance and tensile performance, while the impact performance is poor, which is mainly because the polyurethane modifier can improve the interface bonding between basalt fiber particles and epoxy resin to a certain extent, but the rigidity of the molecular main chain of waterborne polyurethane is low, and it plays the role of toughening agent in epoxy resin polymer, which reduces the rigidity of the system to a certain extent.
[0084] In summary, the epoxy resin glue reinforced by polyaniline-modified basalt fiber particles has good fluidity and excellent processing characteristics, and is suitable for the coating, repair and reinforcement process of irregular devices such as pipelines. In addition, the resin glue can obtain a composite material with outstanding structural properties after a simple temperature treatment, which meets the performance requirements of polymers for pipeline reinforcement.
[0085] Although the resin glues in Comparative Examples 1 and 2 exhibit good fluidity and processability, the comprehensive structural performance of their composite materials is poor and it is difficult to meet the performance requirements of composite materials for pipeline reinforcement; the resin glue in Comparative Example 4 has a large viscosity, which is not conducive to processing operations, and it is impossible to obtain a composite material with outstanding performance through casting and coating.
[0086] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for surface modification of basalt fiber, characterized in that: The method specifically comprises the following steps: 1) Clean the surface of basalt fiber particles with deionized water and dry them for later use; 2) heat treating the basalt fiber particles, cooling them naturally, and then dispersing the fiber particles in acetone and stirring them; The basalt fiber particles treated by desizing and activation are obtained by filtration, separation, washing with deionized water and drying. 3) dissolving polyaniline powder in xylene to obtain a polyaniline solution, adding the basalt fiber particles obtained in step 2) to the polyaniline solution, stirring and blending, centrifuging, standing and air-drying, and then drying to obtain polyaniline-modified basalt fiber particles.
2. The surface modification method of basalt fiber according to claim 1, characterized in that: In step 2), the heat treatment temperature of the basalt fiber is 200-250° C., and the heat treatment time is 1-3 hours.
3. The surface modification method of basalt fiber according to claim 1 or 2, characterized in that: The mass ratio of the fiber particles to acetone is 1:4-8, the stirring treatment time is 20-60 minutes, the drying temperature is 80-100° C., and the drying time is 3-5 hours.
4. The surface modification method of basalt fiber according to claim 1, characterized in that: In step 3), the mass fraction of the polyaniline solution is 0.25-3%, and the mass ratio of basalt fiber particles to the polyaniline solution is 3:8-12.
5. The surface modification method of basalt fiber according to claim 1 or 4, characterized in that: The stirring and blending time is 40-90 minutes, the drying temperature is 100-120° C., and the drying time is 1-3 hours.
6. A polymer-based adhesive, characterized in that: The polymer-based adhesive is a basalt fiber reinforced polymer-based composite glue, which is obtained by adding the surface-modified basalt fiber particles as claimed in claim 1 to epoxy resin and stirring evenly, then ultrasonically treating the mixed system, adding a curing agent, stirring and ultrasonicating.
7. The polymer-based adhesive according to claim 6, characterized in that The curing agent is triethylenetetramine, and the mass ratio of the surface-modified basalt fiber particles in the epoxy resin matrix is 5-15%; the ultrasonic treatment time of the blending system is 40-60 minutes, and the treatment time after adding the curing agent is 5-10 minutes.
8. Use of the polymer-based adhesive as claimed in claim 6 in pipeline reinforcement.
9. A basalt fiber reinforced polymer matrix composite material, characterized in that: The basalt fiber reinforced polymer-based composite glue as claimed in claim 6 is slowly and evenly poured into the mold, left to stand at room temperature for 2-5 minutes, transferred to a drying oven, and cured at 80-100° C. for 40-60 minutes to complete curing and molding, thereby obtaining the basalt fiber reinforced polymer-based composite material.
10. Use of the basalt fiber reinforced polymer matrix composite material as claimed in claim 9 in a pipeline impact-resistant structural bearing member.
Citation Information
Cited By
Multifunctional basalt fiber composite material and preparation method thereof
CN121447938A